Herbal antivirals : natural remedies for emerging & resistant viral infections - Buhner, Stephen Harrod (North Adams, MA : Storey Publishing, 2021)
"In this comprehensive guide, the author profiles the plants that have proven most effective in fighting viral infections and provides in-depth instructions for preparing and using formulations to address the most common infections and strengthen immunity, safely and naturally. The updated 2nd edition also includes an expanded guide to COVID-19"--
Emerging viruses: what we are facing -- Viral respiratory infections and their treatment -- Covid-19 and the coronaviruses -- Viral encephalitis infections and their treatment -- A brief look at some other viruses: from cytomegalovirus and dengue to shingles and their treatment protocols -- Herbal antivirals: the materia medica -- Strengthening the immune system -- Epilogue: What the future holds -- Appendix: A brief look at herbal medicine making..
Includes bibliographical references and index.
110771
Keywords: Herbs -- Therapeutic use; Antiviral agents; Herbal treatments; Therapies